Diffuse idiopathic skeletal hyperostosis (DISH) and its relation to back pain among older men: The MrOS Study - Holton, Kathleen F. (2011)
OBJECTIVES: To estimate the prevalence of diffuse idiopathic skeletal hyperostosis (DISH) in a cross sectional study of elderly men age 65-100 years, and to examine back and neck pain as possible correlates of DISH. METHODS: DISH was defined using Resnick’s criteria and scored according to Mata on lateral spine radiographs of 298 randomly selected participants from the MrOS Study. Standardized self-reported questionnaires were used to assess the frequency and severity of back and neck pain, and the relation of these to DISH status was estimated with Chi-square tests, as well as prevalence ratios (PR) and 95% confidence intervals using log-binomial regression models. RESULTS: DISH was observed in 126 older men (42%), increased with age (30%, 39%, 48%, and 56% for ages 65-69, 70-74, 75-79, and ≥80 respectively), and was positively associated with body mass index (BMI)(p=0.04) and blood pressure (p=0.02). Significantly less back pain in the past 12 months was reported among men with DISH as compared to men without (59% vs. 71%, p=0.03) which remained after adjustment for age, BMI and blood pressure (PR=0.73, 95% CI=0.57-0.95). Back pain severity (p=0.07) and frequency (P=0.06) were also less frequent among men with DISH compared to men without; while reported neck pain was similar between groups (P=0.39). CONCLUSIONS: Among community dwelling elderly men, DISH prevalence is high, increases with age, and is positively associated with BMI and blood pressure. Frequency of self reported back over the past 12 months was lower in older men with DISH as compared to those without DISH.